2015
DOI: 10.1515/ijme-2015-0029
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and Susceptibility to Behavioral Biases among a Sample of Polish Stock Market Investors

Abstract: The aim of this paper is to investigate whether susceptibility to selected behavioral biases (overconfidence, mental accounting and sunk-cost fallacy) is correlated with the Eysenck's [1978] personality traits (impulsivity, venturesomeness, and empathy). This study was conducted on a sample of 90 retail investors frequently investing on the Warsaw Stock Exchange. Participants filled out a survey made up of two parts: 1) three situational exercises, which assessed susceptibility to behavioral biases and 2) an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Our sample contained 84 participants who completed all the tasks and passed the attention checks. Thus, our sample size is similar to previous studies on similar research questions, such as Rzeszutek (2015) with 90 participants or Liêu and Pelster (2020b) with 81 participants.…”
Section: Data Collectionsupporting
confidence: 70%
“…Our sample contained 84 participants who completed all the tasks and passed the attention checks. Thus, our sample size is similar to previous studies on similar research questions, such as Rzeszutek (2015) with 90 participants or Liêu and Pelster (2020b) with 81 participants.…”
Section: Data Collectionsupporting
confidence: 70%
“…Literature on behavioural finance has tried to analyse the behaviour of investors in an effort to improve our understanding on how investors manage their investments (Fatima et al , 2018; Chen et al , 2018; Oehler et al , 2018). Today research has shown how personal characteristics of an individual influence his/her behaviour, perception towards risk and willingness to take risky decisions (Rzeszutek, 2015; Rzeszutek et al , 2015). However, the extent to which these personal characteristics influence investment behaviours and IP has largely remained uninvestigated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature on individual personality traits often focuses narrowly on specific areas such as portfolio selection (Hunter and Kemp, 2004;Bucciol and Zarri, 2015), risk tolerance and investment management (Statman and Wood, 2004;Borghans et al, 2008;Mayfield et al, 2008;Ferguson et al, 2011;Pak and Mahmood, 2015) and money management and financial satisfaction (Ksendzova et al, 2017;Donnelly et al, 2012;Davis and Runyan, 2016). However, few studies focus on the relation between personality traits and exposure to different behavioral biases among stock market investors (Durand et al, 2008;Baddeley et al, 2010;Lin, 2011;Sadi et al, 2011;Zaidi and Tauni, 2012;Rzeszutek, 2015).…”
Section: Personality Traits and Investment Decisionsmentioning
confidence: 99%
“…Baddeley et al (2010) identify an association between Eysenck and Eysenck's (1978) personality traits (impulsivity, venturesomeness and empathy) and the susceptibility to herding behavior among British investors. Similarly, Rzeszutek (2015) investigates whether susceptibility to selected behavioral biases (overconfidence, mental accounting and the sunkcost fallacy) is correlated with Eysenck and Eysenck's personality traits.…”
Section: Personality Traits and Investment Decisionsmentioning
confidence: 99%